Changing the name of diabetes insipidus : a position statement of The Working Group for Renaming Diabetes Insipidus - The Working Group for Renaming Diabetes Insipidus; Hiroshi Arima; Timothy Cheetham; Mirjam Christ-Crain; Deborah Cooper; Mark Gurnell; Juliana B Drummond; Miles Levy; Ann I McCormack; Joseph Verbalis; John Newell-Price; John A H Wass (ENDOCRINE JOURNAL, 2022)
[Abstract. ] "What's in a name? That which we call a rose/By any other name would smell as sweet." (Juliet, from Romeo and Juliet by William Shakespeare). Shakespeare's implication is that a name is nothing but a word and it therefore represents a convention with no intrinsic meaning. Whilst this may be relevant to romantic literature, disease names do have real meanings, and consequences, in medicine. Hence, there must be a very good rational for changing the name of a disease that has a centuries-old historical context. A working group of representatives from national and international endocrinology and pediatric endocrine societies now proposes changing the name of "diabetes insipidus" to "Arginine Vasopressin Deficiency (AVP-D)" for central etiologies, and "Arginine Vasopressin Resistance (AVP-R)" for nephrogenic etiologies. This editorial provides both the historical context and the rational for this proposed name change.